2017
DOI: 10.15666/aeer/1504_14731488
|View full text |Cite
|
Sign up to set email alerts
|

RESPONSE OF TISSUE CULTURED BANANA (Musa acuminate L.) cv. GRAND NAINE TO DIFFERENT LEVELS OF NUTRIENTS UNDER DRIP FERTIGATION AND BLACK PLASTIC MULCH

Abstract: Abstract.A field experiment was carried out in two crop seasons in the lateritic sandy loam soils of Kharagpur, West Bengal, India, to investigate the response of banana (Musa acuminata L.) cv. Grand Naine at different levels of nitrogen, phosphorous and potassium nutrients applications through drip fertigation and plastic mulch. A randomized complete block design was used with four fertigation levels in conjunction with mulch and without mulch. Fertigation levels caused a significant increase in fruit yield a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Helaly et al (2017) observed an increase in plant length, stem diameter and leaf area of husk tomato (Physalis pubescens L.) plants, using black plastic film and white and black compared to the bare soil. Santosh et al (2017) concluded that the treatment 80% of fertilizer requirement application through drip and plastic mulch performed well in respect of growth parameters, maximum plant height, pseudostem girth of banana 'Grand Naine' . According to Chaurasia and Sachan (2020), the black plastic film and the organic mulch provided higher values for plant height and collar diameter than control of squash (Cucurbita pepo L.).…”
Section: Growth Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Helaly et al (2017) observed an increase in plant length, stem diameter and leaf area of husk tomato (Physalis pubescens L.) plants, using black plastic film and white and black compared to the bare soil. Santosh et al (2017) concluded that the treatment 80% of fertilizer requirement application through drip and plastic mulch performed well in respect of growth parameters, maximum plant height, pseudostem girth of banana 'Grand Naine' . According to Chaurasia and Sachan (2020), the black plastic film and the organic mulch provided higher values for plant height and collar diameter than control of squash (Cucurbita pepo L.).…”
Section: Growth Analysismentioning
confidence: 97%
“…This was not observed in this work, but Helaly et al (2017) observed increase in diameter, length, soluble solids and titratable acidity of husk tomato (P. pubescens L.) fruits, cultivated using black plastic film and white and black compared to the bare soil. Santosh et al (2017) concluded that the treatment with 80% of fertilizer requirement application through drip and plastic mulch provided higher levels of soluble solids but a lower titratable acidity of fruits of banana 'Grand Naine' . Eid and El-Kholy (2018) observed an increase in length and diameter of banana fruits 'Williams' , cultivated using black plastic film and organic mulch (banana leaves) under irrigation.…”
Section: Postharvest Qualitymentioning
confidence: 99%